2021
DOI: 10.1038/s42003-021-02177-z
|View full text |Cite
|
Sign up to set email alerts
|

The FlhA linker mediates flagellar protein export switching during flagellar assembly

Abstract: The flagellar protein export apparatus switches substrate specificity from hook-type to filament-type upon hook assembly completion, thereby initiating filament assembly at the hook tip. The C-terminal cytoplasmic domain of FlhA (FlhAC) serves as a docking platform for flagellar chaperones in complex with their cognate filament-type substrates. Interactions of the flexible linker of FlhA (FlhAL) with its nearest FlhAC subunit in the FlhAC ring is required for the substrate specificity switching. To address how… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…The specific (albeit not necessarily direct) interaction of SctG with the large export apparatus component SctV (Fig. 6), which is a key player in substrate selection [5254], supports this hypothesis.…”
Section: Discussionmentioning
confidence: 89%
“…The specific (albeit not necessarily direct) interaction of SctG with the large export apparatus component SctV (Fig. 6), which is a key player in substrate selection [5254], supports this hypothesis.…”
Section: Discussionmentioning
confidence: 89%
“…S1B in the Supplemental material) (6,15,26). FliJ also binds to FlhA C with low affinity (26). It has been shown that CdsO, a FliJ homolog, binds to CdsV C , a FlhA C homolog, at a large cleft between the D4 domains of neighboring CdsV C subunits in the CdsV C ring structure (33).…”
Section: Discussionmentioning
confidence: 99%
“…A complete and irreversible switch would also facilitate the simultaneous assembly of multiple fT3SSs at different assembly stages and ensure that substrates are only secreted at the appropriate stage of assembly. In this respect, recent results of Inoue et al have suggested that the interaction of the flexible linker of FlhA (FlhA L ) with the cytoplasmic domain of FlhA (FlhA C ) might function as a structural switch that might contribute to the specificity switch of the fT3SS from hook-type to filament-type substrate secretion by suppressing the interaction of late substrate-chaperone complexes with FlhA C before hook completion (Inoue et al, 2021). Secondly, it also appears possible that conformational rearrangements within the export apparatus simply enlarge the substrate selectivity spectrum of the fT3SS so that it additionally recognizes and secretes a broader range of substrates: that is, after the switch, the fT3SS recognizes and secretes late substrates in addition to early substrates.…”
Section: Discussionmentioning
confidence: 99%